2019
DOI: 10.1177/1066896919879497
|View full text |Cite
|
Sign up to set email alerts
|

Myxoinflammatory Fibroblastic Sarcoma of Eyeball in an Infant: A Rare Presentation

Abstract: Myxoinflammatory fibroblastic sarcoma (MIFS) is a rare soft tissue neoplasm most commonly occurring in the distal extremities of adult patients. It is a low-grade neoplasm with high rate of local recurrence but low rate of metastasis. We describe a case of MIFS of eyeball in an infant. An enucleation surgery was performed, and on the basis of histopathological and immunohistochemical evaluation, a diagnosis of MIFS was rendered. Till date more than 400 cases of MIFS have been reported with only a single case r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…A small number of cases also occur in children or adolescents, and tumors primarily arise in the soft tissue location of the distal part of the limb ( 1 , 7 ). In this study, we have summarized the clinicopathological features of MIFS reported in the literature in the rare sites (non-bone and soft tissue, since 1998) ( Table 2 ) ( 6 , 8 , 9 ). Clinically, MIFS may be similar to benign lesions and can be often misdiagnosed as the slippery membrane inflammation, ganglion cysts, or giant cell tumor of the tendon sheath.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of cases also occur in children or adolescents, and tumors primarily arise in the soft tissue location of the distal part of the limb ( 1 , 7 ). In this study, we have summarized the clinicopathological features of MIFS reported in the literature in the rare sites (non-bone and soft tissue, since 1998) ( Table 2 ) ( 6 , 8 , 9 ). Clinically, MIFS may be similar to benign lesions and can be often misdiagnosed as the slippery membrane inflammation, ganglion cysts, or giant cell tumor of the tendon sheath.…”
Section: Discussionmentioning
confidence: 99%
“…It often manifests as a painless mass at the distal end of the limb, primarily on the hands and feet, accounting for almost two-thirds of all cases. [4] However, it can occur in multiple body parts, including the iris, [5] parotid gland, [6] maxilla, [7] back, [8] eyeball, [9] nasal dorsum, [10] scalp, [11] and groin. [12] As a result, the World Health Organization (WHO) renamed it myxoinflammatory fibroblastic sarcoma (MIFS) in 2002.…”
Section: Introductionmentioning
confidence: 99%